Preparation of nanosilica powder from rice husk ash by precipitation method - Thuadaij N. (2014)
This work presented a laboratory studies on the preparation of rice husk ash by burning at 700 °C for 3 and 6 h, respectively. Consequently, silica content obtained after heat treatment at 700 °C for 6 h was 98.14%. Rice husk ash (RHA) was purified by alkaline extraction method used 2.0, 2.5 and 3.0 N sodium hydroxide. Percent yield of silica extracted by 2.5 N. NaOH, was 90.3% and the infrared spectral data supported the presence of hydrogen bonded silinol group and the siloxane groups in silica. Subsequently, the RHA was subjected to precipitation method in order to produce nanosilica. The precipitation was done by refluxingsilica from RHA in boiling 2.0, 2.5 and 3.0 N NaOH, respectively. TEM results showed that 2.5 N NaOH for 10 h provided agglomerate particles with dimension of 5-10. The specific surface area was found to be 656 m 2/g. From X-ray diffractograms and diffraction pattern showed that the obtained products were amorphous nanosilica.